2022
DOI: 10.51470/bca.2022.22.2.3845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seaweed extract and Evisect 50 WP pesticide on the population density of Bemisia tabaci and some characteristics of eggplant growth

Abstract: The field experiment conducted at 2019 ingreenhouse of the college of agriculture, University of Anbar to study the effect of seaweed extracts and Evisect 50 WP pesticide on the population density of whitefly Bemisia tabaci and some characteristics of eggplant Solanum melongena L. growth. The population density nymphs and adults rate decreased at use the seaweed extracts after 60 days of transplanting compared with control treatments. This effect was reflected in increased of some vegetative characteristics as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Post-harvest losses in maize involve degradation in both quantity and quality from harvest to consumption" [5]. "Poor post-harvest handling, infrastructure, weather variability, bacteria, viruses, fungi, and biotic factors such as insects and pests, often worsen such losses" [10,26,46]. "It has been observed that, insect infestation is the greatest cause of losses of stored grains globally.…”
Section: Introductionmentioning
confidence: 99%
“…Post-harvest losses in maize involve degradation in both quantity and quality from harvest to consumption" [5]. "Poor post-harvest handling, infrastructure, weather variability, bacteria, viruses, fungi, and biotic factors such as insects and pests, often worsen such losses" [10,26,46]. "It has been observed that, insect infestation is the greatest cause of losses of stored grains globally.…”
Section: Introductionmentioning
confidence: 99%